SELF-ATTITUDE TOWARDS SKIN HEALTH IN ADOLESCENTS - Irmazida, Nela Hilmiana; Apriliana, Eka Rida; Al Zuhrah, Nurul Faridah; Febriarta, Ajie; Wahyuni, Putri; Quraini, Annisa; Yulanda, Prasetyani Fitri; Setiyowati, Eppy (Transpublika Publisher, 2022)
Teenagers frequently underestimate and disregard personal hygiene, which has a negative impact on health. The aim of this study was to analyze self-attitude towards skin health in adolescents. This study employs descriptive analytic techniques. The sample was selected by simple random sampling technique, namely probability sampling with the Spearman test statistic. A sample of 36 teenage respondents in the Mulyorejo Baru area, Surabaya City. The results showed that 0 respondents (0%) had good self-esteem with good skin health, 1 respondent (2.8%) had good self-esteem with good skin health, had a good attitude towards health bad skin as much as 0 respondents (0%). Then, for students with adequate self-esteem and good skin health, there were as many as 23 respondents (63,9%), adequate self-esteem with moderate skin health, as many as 6 respondents (16,7%), and adequate self-esteem with bad skin health, there were as many as 0 respondents (0%). From the research that has been done, it can be concluded that the self-esteem of adolescents in the Mulyorejo Baru area, Surabaya City and skin health does not have a significant relationship based on the Spearman test p: 0,294.